InterGEO: a digital platform for university education on geomorphological heritage - Reynard, Emmanuel (2018)
The project InterGEO was carried out with the objective to disseminate knowledge on geomorphological heritage by developing a digital learning platform. It aims at improving students' autonomy by the reduction of face-to-face teaching and increasing autonomous learning as well as promoting international interactions between students interested in geomorphological heritage. A completely free-access virtual course on geomorphosites was developed with the Learning Management System Moodle. The course is divided into 24 thematic chapters, each of them containing a short description, a list of references and selected publications, as well as other educational material (videos, virtual fieldtrips, etc.). In particular, several videos allow presenting in a dynamic way concepts and examples. The paper presents the tool and its use in academic programmes in six European universities, where it was tested, in various contexts (Bachelors' and Masters' programmes; students in geography or geology; general courses in geomorphology and specific courses on geoheritage and geoconservation), before discussing the advantages and challenges the tool is facing. The InterGEO platform is an easy-to-use and friendly educational tool, which allows developing blended learning activities; it is flexible and adaptable in various learning contexts.